Development of Enrichment Book on the Wayang Banjaran Bima Stories of Based on Drama Text with a Character Education for High School / Vocational School (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to describe the characteristics of the needs and development models on the â€œWayang Banjaran Bimaâ€ Stories of Based on Drama Text with a Character Education for High School / Vocational School. The study is conducted by using research and development design. The enrichment book is developed by applying the feasibility aspects of it, book consisting of four aspects namely material, linguistic, presentation, and graphic. In addition, enrichment book products are arranged in accordance with the principles of preparation of enrichment books such as having conformity with educational goals, adjusting to the development of science, and developing the ability to reason. The draft enrichment book consists of the beginning, contents, and last. The enrichment book development of products are based on the characteristics of the students needs who expect the preparation of puppet story material based on drama texts and there is a character education content. The puppet story is developed in the form of a drama script text divided into six the Banjaran Bima plays, namely (1) Bima Bungkus, (2) Bale Sigala-gala, (3) Dewa Ruci, (4) Bima Suci, (5) Jagal Abilawa, and ( 6) Pandhu Swarga. The content of character education is inserted into the whole story in the conclusion section at the end story. With the content of character education students are expected to be able to understand the values contained in the puppet story and it can be applied in everyday life.